Factores que inciden en las habilidades sociales de las y los alumnos del primer grado de secundaria del c.e.m. gustavo ries, trujillo - 2014. - Gonzales Baca, Deysi (2015)
This research focuses on explaining FACTORS AFFECTING THE SOCIAL SKILLS AND THE STUDENTS OF FIRST DEGREE OF SECONDARY CEM "GUSTAVO RÍES" TRUJILLO-2014. This study was conducted with a total of 200 students, consisting of 8 sections; of first "A" to first "H", with an average of 25 students per section. Statistical, inductive-deductive, analytical, and ethnographic: in research methods were used. Survey depth interview and review of literature sources and the following techniques are also used. Through the instruments questionnaire depth interview guide and index cards. To this it has been based on the following theoretical approaches: gender, needs a human scale, human development, theory of family social support, social learning theory. Their results show a profile of young people who have specific deficiencies in the issue of social skills have developed with them to have a better development in the social and professional level. Hindering the achievement of emotional intelligence in the workplace, professional skills, teamwork, identification with the goals of a company, and his leadership at work. However, it does have a specific scale values, allowing them to have a closer relationship with his friends, where solidarity prevail, spirit to get ahead in life, and identification with the effort made by their parents.